Development and Characterization of An Unshielded PatLoc Gradient Coil for Human Head Imaging. Issue 4 (18th October 2013) - Welz, Anna; Cocosco, Chris; Dewdney, Andrew; Gallichan, Daniel; Jia, Feng; Lehr, Heinrich; Liu, Zhenyu; Post, Hans; Schmidt, Hartmut; Schultz, Gerrit; Testud, Frederik; Weber, Hans; et al.
Abstract: A cylindrical head gradient insert for human imaging with non‐linear spatial encoding magnetic fields (SEMs) has been designed, optimized and successfully integrated with a modified 3T clinical MR system. This PatLoc (parallel acquisition technique using localized gradients) SEM coil uses SEMs that resemble second‐order magnetic shim fields, but with much higher amplitude as well as the possibility for rapid switching. This work describes the optimization of a coil design and measurement methods to characterize its SEMs, induced self‐eddy currents and concomitant fields. Magnetic field maps of the SEMs are measured and it is demonstrated that the induced self‐eddy current magnetic fields are small and can be compensated. A method to measure concomitant fields is presented and those fields are compared to simulated data. Finally, in vivo human images acquired using the PatLoc system are presented and discussed. © 2013 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 43B: 111–125, 2013